The calcium-sensing receptor in heart physiology and development of endothelin-1-dependent hypertrophy - Dyukova, Elena; Justus Liebig University Giessen (My University, 2016)
Background. Ca2+ is commonly known as a crucial molecule in heart tissue. It triggers signal transduction, cellular contractility, and activates enzymes. Moreover, Ca2+ is considered to be an important second messenger in cardiovascular tissue. Recently, Ca2+ ions were shown to act as a first extracellular messengers via special calcium-sensing receptors (CaR). These receptors are G protein-coupled and are present in many organs and tissues throughout the entire body including the cardiovascular system. They are supposed to activate several signaling cascades in cardiomyocytes. In the past few years, the involvement of CaR in heart diseases was shown in many publications. CaR are involved in ischemia-reperfusion injury, hypertension, hypertrophy and heart failure development. However, underlying mechanisms remained elusive so far. Thus in present study we aimed to investigate on the role of CaR in physiological heart function and during the development of cardiac hypertrophy.Materials and Methods. Experiments were performed on isolated cardiomyocytes and heart muscle strips. Load-free cell shortening was measured with a special cell-edge detection system. Contraction force of the heart muscle strips was measured using tensometry equipment. Cells and tissue material were exposed to Western Blot and RT-PCR analysis. Ca2+-transients were detected in isolated cardiac myocytes loaded with FURA-2AM by ION Optix system. To determine protein kinase C (PKC) activity under CaR stimulation, special nonradioactive PKC activity assay was used. Hypertrophy was modulated in vivo and in vitro. As in vivo model rats with NO-deficiency were used. Hypertrophy in vitro was provoked by adding ET-1 and PE to the cardiomyocytes culture for 24 h. Polyamines putrescine and spermine and synthetic CaR agonist gadolinium (Gd) were used to activate CaR and NPS2390 and siRNA vs CaR to antagonize the receptor.Results. CaR in physiological heart function. RT-PCR and Western Blot analysis confirmed the presence of the receptor in adult rat cardiomyocytes. Differences in CaR expression between right and left ventricular and atrial tissues were detected. Cells and heart muscle strips shortening as well as relaxation velocity of cardiomyocytes increased under CaR activation. Inhibition of the receptor lead to a reduced contraction force of the heart strips and decreased load-free cell shortening of cardiomyocytes, and also to a deceleration of the relaxation velocity. Significant effect of CaR inhibition was observed just under physiological Ca2+-concentrations. The effect of CaR agonists and inhibitors on atrial strips was less pronounced. Systolic Ca2+ and Ca2+-uptake to the sarcoplasmic reticulum (SR) were enhanced under CaR activation. Putrescine increased the activity of PKC and the levels of phosphorylated phospholamban (PLB). Moreover, inhibition of PKC abolished the effect of CaR activation on load-free cell shortening and relaxation velocity of cardiomyocytes. Effect of CaR was also abolished under downregulated RAMP1. CaR and hypertrophy. Hypertrophy developed in vivo was accompanied by increased mRNA levels of CaR and RAMP1. Interestingly, the mRNA of ETB receptors was also enhanced in one month L-NAME treated rats, whereas ETA and ECE showed no differences.ET-1 and PE chronic stimulation decreased shortening and relaxation velocity of the cells. However, the effect of ET-1 was potentiated by NPS2390 and siRNA vs CaR. Enhanced CaR protein expression was shown under ET-1 exposure for 24 hours, but not under PE stimulation. Inhibition of ETB1 and ETA receptors cancelled ET-1 remodeling effect and enhanced CaR protein expression. Conclusion. Cardiomyocytes express CaR under physiological conditions and this contributes to the basal electromechanical coupling of cardiomyocytes under nearly physiological Ca2+concentrations. Activation of the receptor with direct agonists is able to further increase contractility. It is also leading to the enhanced relaxation velocity which is explained by PKC activation, PLB phosphorylation and enhanced SERCA activity. To be functionally expressed on cardiomyocytes membrane, CaR require the activity of RAMP1.During the development of pressure induced hypertrophy, ET-1 via ETA or ETB1 receptors is able to upregulate CaR expression. Elevated levels of CaR are supposed to compensate a loss of the heart function during hypertrophy development.

Hintergrund: Ca2+ ist ein wichtiges Molekül für die kardiale Funktion. Es triggert Signaltransduktion, Kontraktilität und aktiviert Enzyme. Ca2+ kann als wichtiger sekundärer Transmitter betrachtet werden. Allerdings wirkt Ca2+ auch als erster Signalbotenstoff durch Bindung an den Calcium-Sensing-Rezeptor (CaR). CaR sind G-Protein gekoppelte Rezeptoren, die sich in vielen Organen des Körpers finden. CaR sind an der Entstehung von Reperfusionsschäden, Hypertension, Hypertrophie und Herzinsuffizienz beteiligt. Die zugrunde liegenden Mechanismen sind weniger klar und Gegenstand dieser Untersuchungen.Material und Methoden: Funktionelle Untersuchungen wurden an isolierten Kardiomyozyten und Muskelstreifenpräparaten durchgeführt. Die lastfreie Zellverkürzung isolierten Herzmuskelzellen wurde mit Hilfe eines Zellendendetektionssystems bestimmt. Zell- und Gewebeanalysen wurden auch mittels Western Blot und RT-PCR Technik durchgeführt. Calcium-Transienten wurden unter FURA-2AM Beladung der Zellen bestimmt. Proteinkinase C Aktivität wurde mittels nicht-radioaktiven Detektionssystemen (ELISA) bestimmt. Als in vivo-Modell der kardialen Druckbelastung wurden Ratten mit NO-Defizienz untersucht. Zelluläre Hypertrophie wurde durch Zugabe von Phenylephrin und Endothelin ausgelöst. CaR Stimulation erfolgte durch Putrescin und Gadolinium. Ergebnisse: CaR unter physiologischen Bedingungen: RT-PCR und Western-Blot Analysen bestätigten eine konstitutive Expression des CaR in adulten Rattenkardiomyozyten. Die stärkste Expression fand sich im linken Ventrikel. CaR Aktivierung führte zur Zunahme der Verkürzung und Relaxationsgeschwindigkeit von Kardiomyozyten und Muskelstreifen. Am stärksten beeinflusste CaR-Stimulation die Zellverkürzung bei nahezu physiologischer Ca2+-Konzentration. Effekte durch Stimulation des CaR waren am Vorhof weniger ausgeprägt. Die Ca2+-Transienten waren unter Stimulation des CaR verbessert. Putrescine aktivierte die Proteinkinase C und bei Hemmung der Proteinkinase C waren die positiv inotropen Wirkungen der CaR-Stimulation unterdrückt.CaR und Hypertrophie: In dem hier verwendeten Hypertrophie-Modell kam es in vivo zu einer verstärkten Expression von CaR und RAMP1. Interessanterweise nahm auch die Expression des ETB Rezeptors zu. Langfristig führte eine Exposition der Zellen mit ET-1 zu einer Abnahme der lastfreien Zellverkürzung, aber der Effekt war viel ausgeprägter unter Hemmung des CaR oder nach Herabregulation des Rezeptors. Pharmakologische Experimente zeigen, dass eine Stimulation der ETA- oder ETB1-Rezeptoren die negativen Effekte von Endothelin-1 durch Induktion des CaR begrenzen.Schlussfolgerung: Kardiomyozyten exprimieren konstitutiv einen CaR der zur basalen Zellverkürzung beiträgt. Eine Aktivierung des CaR führt zur Verstärkung der Zellverkürzung, durch Proteinkinase C-abhängige Phosphorylaierung von Phospholamban und nachfolgender Verbesserung der Ca2+-Transienten. Kardiomyozyten benötigen RAMP1 zur Verankerung des Rezeptors an der sarkolemmalen Membran. Bei prohypertropher Stimulation mit Endothelin-1 kann eine Heraufregualtion des CaR zur partiellen Kompensation eines hypertrophie-bedingten Funktionsverlustes beitragen.
Keywords: ddc:610